2014
DOI: 10.1084/jem.20130968
|View full text |Cite
|
Sign up to set email alerts
|

Epitope-specific antibody response is controlled by immunoglobulin VH polymorphisms

Abstract: Epitope-specific antibody responses recognized by germline-encoded structures are of significant relevance for the development of autoantibody-mediated autoimmune diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…We can thus compare how the same linear epitope is bound by ACC4 (C1 CIT360 ) and ACC1 (C1 CIT365 ) but with different modification states. The other two structures comprise the Fab-peptide complexes of the anti-CII antibodies CIIC1 (20) and M2139 (22), which recognize the native, i.e., triple-helical and unmodified, C1 and J1 epitopes of CII, respectively. Comparisons of these structures may allow identification of determinants of the conformational selectivity, i.e., single-chain versus triple-helical epitopes, of these antibodies.…”
Section: Comparison Of CII Epitope Binding By Other Acpas and Anti-cimentioning
confidence: 99%
“…We can thus compare how the same linear epitope is bound by ACC4 (C1 CIT360 ) and ACC1 (C1 CIT365 ) but with different modification states. The other two structures comprise the Fab-peptide complexes of the anti-CII antibodies CIIC1 (20) and M2139 (22), which recognize the native, i.e., triple-helical and unmodified, C1 and J1 epitopes of CII, respectively. Comparisons of these structures may allow identification of determinants of the conformational selectivity, i.e., single-chain versus triple-helical epitopes, of these antibodies.…”
Section: Comparison Of CII Epitope Binding By Other Acpas and Anti-cimentioning
confidence: 99%
“…Interestingly, in the mouse the highly pathogenic antibodies to type II collagen (CII) are not negatively selected but rather contain an expanded germline-encoded B cell response, and this phenomenon has been associated with several MHC class II and Ig-V alleles [23][24][25]. Thus, avidity maturation (and pathogenicity) may not necessarily involve germinal center selection and somatic mutations, but might still be promoted by T-cell help.…”
Section: Stage 1 -Autoimmune Priming In Healthy Individualsmentioning
confidence: 99%
“…However, as it is easier to crystallize antibodies with high affinity, these examples might not be representative of the full repertoire of RA associated RFs. In addition, the possible occurrence of somatic mutations needs to be analyzed by sequencing the correct V gene from the same individual that antibody was derived from to ensure that mutations are not due to individual allelic differences.In animal models high titers of ACPAs have so far not been demonstrated, whereas RFs occur in the collagen-induced arthritis (CIA) [20], pristane-induced arthritis (PIA) [21], and the SKG (with a ZAP70 mutation) [22] type II collagen (CII) are not negatively selected but rather contain an expanded germline-encoded B cell response, and this phenomenon has been associated with several MHC class II and Ig-V alleles [23][24][25]. Thus, avidity maturation (and pathogenicity) may not necessarily involve germinal center selection and somatic mutations, but might still be promoted by T-cell help.…”
mentioning
confidence: 99%
“…We also showed that B-cell hybridomas generated from B10Q.ACB mice lack somatic mutations in the IgH and L chains, which might operate as a protective mechanism to avoid high affinity autoimmune responses. All the investigated CII-specific pathogenic antibodies so far, including the CB20-used for generating the ACB mouse, bind to CII using germ line-encoded binding sites [14,34]. Hence, we suggest that the CII reactivity is encoded in the natural repertoire and may also have a regulatory function in a physiological context [35].…”
Section: Discussionmentioning
confidence: 91%
“…The most striking observation that was associated with the development of arthritis in the ROS deficient mice was the intra-molecular epitope spreading. Although the triple helical CII molecule is partly repetitive in its amino acid sequence, the repetitive glycines in every third position are not on the surface of the molecule and hence do not participate in antibody binding [14,18,34]. Thus, the antibodies bind unique structures and the epitope spreading cannot be explained by cross-reactivity of antibodies.…”
Section: Discussionmentioning
confidence: 99%